Food insecurity and its determinants in a vulnerable area of Santiago, Chile - Pinheiro, Anna Christina; Quintiliano-Scarpelli, Daiana; Araneda-Flores, Jacqueline; Oliveira, Rogerio Antonio de; Pizarro, Tito; Suarez-Reyes, Mónica; Marques de Oliveira, Maria Rita (Frontiers in Sustainable Food Systems, 2022)
This study aims to analyze the determinants of Food Insecurity for a group of households composed of schoolchildren and their caregivers/guardians living in a low-to-medium Community Development Index area of the city of Santiago, Chile with a high presence of migrant population. The non-probabilistic and convenience sample was made up of 646 people, who answered a series of surveys with the aim of characterizing this group in sociodemographic terms (sex, age, number of inhabitants in the household, place of food purchase, conditional or non-conditional state transfer program beneficiary status, purchase, maternal education level and basic knowledge of food and nutrition). To assess moderate-to-severe food insecurity and severe food insecurity, the Food Insecurity Experience Scale-FIES was used between September and October 2021. Logistic regression tests were used to carry out multivariate analyzes, with the use of stepwise back-and-forward strategies for the selected variables and defining p<0.05. These models were adjusted per number of inhabitants in the household. The results indicate that 25.4% of households suffer from moderate-to-severe food insecurity, and 6.4% severe food insecurity. The factors that most influenced the risk of food insecurity were being a migrant, a maternal education level lower than complete primary education, a performance of less than 75.0% on a basic food and nutrition knowledge test, and when the father is responsible for food purchases. Several public policies have been implemented in Chile during the most recent decades aimed towards increasing access to healthier foods and the implementation of healthier food environments. Despite this, there still are social and economic health determinants that contribute to the risk of the food security for the most vulnerable groups in the country, thus putting the fulfillment of the human right to adequate food at risk.